(untitled) (ENTHYMEMA, 2025)
This paper examines the role of sound as a narrative device in the films of Austrian-American director Fritz Lang. Incorporating several methodological treatments of audio, as well as classic literary narratology and media studies, the acoustics and spatial landscapes of Lang’s filmography and its narratives are analysed, establishing ways in which sound helps Lang build theme, mood, and meaning. After his early intermedial avant-garde experiments, the director’s technique of constructing complex sonic environments gradually evolved into a more simplified, and at times even mundane, auditory landscape that can be observed in his later films. This shift is indicative of the overall development of sound usage in cinema, but it also relates to Lang’s career trajectory as he fled Germany for the U.S. to be at the forefront of establishing film noir. Despite these later developments, Fritz Lang remains one of the first directors to achieve a meaningful unity of sound and image, reinventing the film experience.